What bankers know, or ought to know, about foreign exchange theory - EINZIG, P. (PSL Quarterly Review, 2014)
Foreign exchange dealers and senior bank officials are still inclined to think that their operations must exclusively rely on experience, common sense and intuition, and must avoid being “contaminated” by foreign exchange rate theory. This is a relatively recent trend that only began after the First World War, while in the past centuries many bankers engaged in practical foreign exchange operations were not only aware of theoretical relations, but in many instances actually formulated them. The present article reviews the history of some such examples, and considers the most basic determinants of the exchange rate of which bankers and dealers, although unaware of the theoretical relations, are in practice familiar. The problem is to be able to know when each theory is valid and when it becomes expedient to shift the theoretical bases of foreign exchange operations. JEL: